Relax, Keep Walking — A Practical Guide to Continuous Phylogeographic Inference with BEAST. (2nd February 2021) - Dellicour, Simon; Gill, Mandev S; Faria, Nuno R; Rambaut, Andrew; Pybus, Oliver G; Suchard, Marc A; Lemey, Philippe
Abstract: Spatially explicit phylogeographic analyses can be performed with an inference framework that employs relaxed random walks to reconstruct phylogenetic dispersal histories in continuous space. This core model was first implemented 10 years ago and has opened up new opportunities in the field of phylodynamics, allowing researchers to map and analyze the spatial dissemination of rapidly evolving pathogens. We here provide a detailed and step-by-step guide on how to set up, run, and interpret continuous phylogeographic analyses using the programs BEAUti, BEAST, Tracer, and TreeAnnotator.